Innovative security solutions for information technology and communications : 9th International Conference, SECITC 2016, Bucharest, Romania, June 9-10, 2016, Revised selected papers /: 9th International Conference, SECITC 2016, Bucharest, Romania, June 9-10, 2016, Revised selected papers. (2016) - Unknown
No abstract available